ANALYSIS OF THE READINESS FOR EDUCATION 4.0 TRANSFORMATION IN INDONESIA AND TÜRKIYE - Luthfi Fadilah; Achmad Ardiansyah (IEC: Journal of Educational Innovation, 2025)
This article examines the readiness of Education 4.0 transformation in Indonesia and Türkiye through a comparative qualitative literature review. Education 4.0 emphasizes the integration of digital technology, innovative pedagogy, and the development of 21st-century skills in response to the challenges of the Industrial Revolution 4.0. Employing a descriptive qualitative approach with library research methods, this study analyzes national and international literature published between 2020 and 2025 to identify patterns of curriculum policy, technology integration, and teacher readiness in both countries. The findings indicate that Indonesia and Türkiye share common structural challenges, particularly related to unequal access to technological infrastructure and varying levels of teacher readiness across regions. At the same time, differences emerge in policy orientation and implementation strategies, where Indonesia places greater emphasis on curricular flexibility and pedagogical reform through the Merdeka Curriculum, while Türkiye prioritizes large-scale national technology initiatives, such as the Turkish Century Education Model, the FATİH Project, and the Education Information Network (EBA), to support digital learning. The study concludes that both countries remain in a transitional phase toward Education 4.0, and that a more integrated alignment between curriculum reform, teacher capacity development, and technology provision is essential to strengthen sustainable pedagogical transformation in developing country contexts.